Relação intertemporal entre receitas e despesas públicas: uma análise em painel para os estados brasileiros - Ribeiro, Gerson da Silva (2020)
This paper analyzes the intertemporal relationship between public revenues and expenditures forBrazilian states considering the period between 1996 and 2016. The analysis of causality betweentax revenues and total expenditures is the primary interest, being investigated from the perspectiveof the four hypotheses prevalent in the theoretical literature and empirical public finance: tax-spend, spend-tax, fiscal synchronism and institutional separation. The econometric instrumentused is characterized by the application of an error correction model for panel data, as well asby the use of tests that consider the possibility of heterogeneity and transversal dependencebetween the states. In order to control how indebtedness and dependence on transfers from theUnion affect the dynamics between income and expenditure, subsamples that separate states withlow/high indebtedness and level of dependence were analyzed. In general, the results obtainedsupport the hypothesis to tax-spend. A positive variation of 10%in the longterm coefficientof tax revenue corresponds to an increase of approximately 3%in total expenses. In addition,Granger’s short-term causality tests report that the tax revenue coefficients are jointly significantin the expense equation thus representing past values of tax revenues help to explain presentvalues of expenses.